The adoption of digital currency electronic payment in China - Wei Yizhen; Amer Azlan Abdul Jamal (Faculty of Business, Economics and Accountancy, UMS, 2022)
The misuse of unregulated digital currency with the absence of regulation is recognized by the central banks worldwide. In response to this, the Central Bank Digital Currency (or CBDC), a regulated digital currency was developed which have many advantages over unregulated digital currency. In China, the Digital Currency Electronic Payment (DC/EP or “digital yuan”) was introduced in 2014 with the aim to improve its monetary and financial supervision. To date, the development of the effectiveness and acceptance level of DC/EP among the people of the Republic of China is still at the infant stage after it underwent its first trial in 2019. Using mixed method design, this study aims to develop the conceptual framework based on combination of two underpinning theories namely Theory of Reasoned Action (TRA) and Theory of Acceptance Model (TAM). The outcomes of this research provide a theoretical basis for future research on the implementation of Digital Currency Electronic Payment.